2021
DOI: 10.1002/jcsm.12741
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analysis of genome‐wide DNA methylation and integrative omics of age in human skeletal muscle

Abstract: Background Knowledge of age‐related DNA methylation changes in skeletal muscle is limited, yet this tissue is severely affected by ageing in humans. Methods We conducted a large‐scale epigenome‐wide association study meta‐analysis of age in human skeletal muscle from 10 studies (total n = 908 muscle methylomes from men and women aged 18–89 years old). We explored the genomic context of age‐related DNA methylation changes in chromatin states, CpG islands, and transcription factor binding sites and performed gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 54 publications
(76 citation statements)
references
References 67 publications
3
71
1
1
Order By: Relevance
“…While FOXO3 skeletal muscle gene expression differs between males and females, it seems that the direction is opposite in young and old individuals, which emphasizes the caution that should be used when interpreting sex differences across a large age range of individuals. Interestingly, FOXO3 was hypomethylated in skeletal muscle with age in a recent study from our group [ 97 ]. Regions with differential DNA methylation in the three validated genes were located in enhancers (FOXO3 and ALDH1A1) and regions of strong transcription (GGT7), suggesting that subsequent transcription may be altered.…”
Section: Discussionmentioning
confidence: 80%
“…While FOXO3 skeletal muscle gene expression differs between males and females, it seems that the direction is opposite in young and old individuals, which emphasizes the caution that should be used when interpreting sex differences across a large age range of individuals. Interestingly, FOXO3 was hypomethylated in skeletal muscle with age in a recent study from our group [ 97 ]. Regions with differential DNA methylation in the three validated genes were located in enhancers (FOXO3 and ALDH1A1) and regions of strong transcription (GGT7), suggesting that subsequent transcription may be altered.…”
Section: Discussionmentioning
confidence: 80%
“…23 Since then, it has been confirmed that the methylation status of approximately 200 CpG sites can accurately predict chronological age in skeletal muscle tissue. 24,25 We extended these findings using technology allowing greater coverage of 850,000 CpG sites in skeletal muscle tissue, as well as isolated skeletal muscle-derived stem cells, from older (mean, 83 years) versus young adults (mean, 27 years). 26 Indeed, we also demonstrated an accumulation of methylation (hypermethylation) in both aged muscle tissue and isolated muscle-derived stem cells, with tissue displaying enriched hypermethylation in load-/growth-associated gene pathways such as focal adhesion and mTORC signaling and isolated cells displaying this enrichment in genes within the calcium signaling pathway.…”
Section: Epigenetics Muscle and Agingmentioning
confidence: 87%
“…Ageing is associated with DNA methylation changes in all human tissues, and epigenetic markers can estimate chronological age based on DNA methylation patterns [22]. Together with others we have recently helped developed a muscle-specific epigenetic clock (muscle-specific epigenetic age test, or ‘MEAT’) that predicts age with better accuracy than the pan-tissue epigenetic clock [31, 32]. Therefore, for the analysis of DNA methylation age (DNAm Age), we extracted the β-values from normalized data, as previously described.…”
Section: Methodsmentioning
confidence: 99%
“…This is because, with age, it is proposed that our cells (including SkM [27-29]) accumulate methylation [22, 30] and therefore become ‘hypermethylated’. Meta-analysis of the SkM methylome also identified that hypermethylation predominantly occurs in gene regulatory regions with advancing age [31, 32]. In contrast, both acute exercise and chronic training have been shown to decrease methylation (i.e., hypomethylation) in both human and mouse SkM [17, 18, 33-35].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation